The Reliability Analysis of Rotary Klin B - Tumanggor, Agustina; Purnomo, Joko; Rizki, Muhammad (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2020)
XYZ is a company engaged in the production of iron ore into semi-finished products (Iron Reduction). The machine company has a very important and vital role to support the production process. Rotary Kiln is a place where iron ore reduction occurs, the result of which is called an iron reduction kiln or commonly known as sponge iron. By looking at the constraints at PT. XYZ on its production machines often breakdowns, which is a fundamental reason for researchers to increase the reliability level of the rotary kiln b PT XYZ production machine. XYZ. The research was carried out on the Rotary Kiln B machine made in Germany which plays a high enough role in the company. The research objective was to analyze the reliability (reliability) of Rotary Kiln b at PT. XYZ. The method used is Reliability with the Mean Time to Repair (MTTR) method. From the calculation of reliability on Rotary Kiln B with an operating time of 289 hours, the results are 0.5371 and MTTR 537.7732. The higher the reliability value, the better the machine used in the operation process.